Restytucja mienia osób represjonowanych po powstaniu węgierskim 1956 r. – analiza cywilnoprawna - Bucoń, Paweł (PRAWO i WIĘŹ, 2026)
The article discusses the civil law aspects of property restitution for persons repressed after the 1956 Hungarian Uprising. The policy of the communist government, created as a result of the Soviet invasion, aimed to impose numerous repressive measures on participants in the uprising and all those deemed enemies of the “people’s government”. A key element of this was the confiscation of property. Therefore, after the overthrow of the communist regime in 1989, the question arose as to how to implement the restitution of property seized from its original owners. This process was limited in nature and consisted of providing compensation in the form of so-called compensation vouchers. In the author’s opinion, these vouchers did not fully fulfill their role as a compensation instrument. However, the limited scope of compensation was justified by the need to protect acquired rights, ensure the stability of property relations, and address state budget constraints.